Enzymatic production of 4-cholesten-3-one using cholesterol oxidase from Bacillus cereus strain KAVK5 and its potentiality toward the inhibition of disease-associated proteins an in silico approach - Kokila Vasanthakumar,, Amutha Kuppusamy (Journal of Applied Pharmaceutical Science, 2022)
The biological conversion of cholesterol into 4-cholesten-3-one (4-CHN), with the help of commercially important cholesterol oxidase (CHO) originated in Bacillus cereus strain KAVK5 from ghee, has been explored in this study. 4-CHN is extensively studied in the field of medicine. This research work aimed to optimize CHO productivity from KAVK5, which is employed to produce 4-CHN. Qualitative and quantitative methods examined CHO production and the modification of the fermentation medium increased its productivity. It was optimized using components such as xylose, peptone, sodium nitrate, and manganese sulfate with pH 7.0 maintained at 30°C for 32 hours of incubation. KAVK5 markedly yielded a superior level of CHO (1.86 U/ml) in an optimized media, and the molecular weight was achieved to be 32.8 kDa. In addition, the bioconversion process was implemented by the double-phasic system, i.e., aqueous and organic. The report affirmed that 1.23 g of 4-CHN was yielded for every bioconversional process. An in silico docking study was carried out using the receptors associated with obesity, diabetes, cancer, and bactericidal disorders. The outcome of this report declared that an activated ligand 4-CHN is treated as the best therapeutic agent to treat diseases.
Keywords: 4-cholesten-3-one, Bacillus cereus strains KAVK5, bioconversion, cholesterol oxidase, docking, optimization